Handling of Incidents in the Clinical Application of Ionizing Radiation in Diagnostic and Interventional Radiology – a Multi-center Study - Müller, Birgit Sabine; Singer, Julian; Stamm, Georg; Pirl, Lukas; Borowski, Markus; Hertlein, Thomas; Rerich, Eugenia; Trinkl, Sebastian; Wucherer, Michael; Ammon, Josefin (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose According to the German legislation and regulation of radiation protection, i. e. Strahlenschutzgesetz und Strahlenschutzverordnung (StrlSchG and StrlSchV), which came into force on 31st December 2018, significant unintended or accidential exposures have to be reported to the competent authority. Furthermore, facilities have to implement measures to prevent and to recognize unintended or accidental exposures as well as to reduce their consequences. We developed a process to register incidents and tested its application in the framework of a multi-center-study.Materials and Methods Over a period of 12 months, 16 institutions for x-ray diagnostics and interventions, documented their incidents. Documentation of the incidents was conducted using the software CIRSrad, which was developed, released for testing purposes and implemented in the frame of the study. Reporting criteria of the project were selected to be more sensitive compared to the legal criteria specifying “significant incidents”. Reported incidents were evaluated after four, eight, and twelve months. Finally, all participating institutions were interviewed on their experience with the software and the correlated effort.Results The rate of reported incidents varied between institutions as well as between modalities. The majority of incidents were reported in conventional x-ray imaging, followed by computed tomography and therapeutic interventions. Incidents were attributed to several different causes, amongst others to the technical setup and patient positioning (19 %) and patient movement or insufficient cooperativeness of the patient (18 %). Most incidents were below corresponding thresholds stated in StrlSchV. The workload for documenting the incidents was rated as appropriate.Conclusion It is possible to monitor and handle incidents complient with legal requirements with an acceptable effort. The number of reported incidents can be increased by frequent trainings on the detection and the processing workflow, on the software and legal regulation as well as by a transparent error handling within the institution.Key Points: Citation FormatZiel Entsprechend dem zum 31. Dezember 2018 in Kraft getretenen Strahlenschutzgesetz und der -verordnung (StrlSchG und StrlSchV) sind bedeutsame Vorkommnisse bei der Anwendung ionisierender Strahlung der zuständigen Behörde zu melden. Zudem sind Maßnahmen zu treffen, um Vorkommnisse zu vermeiden, zu erkennen und deren Auswirkungen so gering wie möglich zu halten. Im Rahmen einer Multi-Center-Studie wurde ein Verfahren zur Erfassung von Vorkommnissen entwickelt und dessen Anwendung getestet.Material und Methoden Über einen Erfassungszeitraum von 12 Monaten dokumentierten 16 verschiedene röntgendiagnostische Einrichtungen Interventionsschwellenüberschreitungen (IntS-Überschreitungen). Zur Dokumentation der IntS-Überschreitungen wurde die Software CIRSrad entwickelt und in den teilnehmenden Einrichtungen implementiert. Die Kriterien zur Definition einer IntS-Überschreitung lagen größtenteils unterhalb der Definition eines Vorkommnisses nach der StrlSchV und wurden weiter gefasst. Alle gemeldeten IntS-Überschreitungen wurden nach 4, 8 und 12 Monaten ausgewertet. Abschließend wurden die Studienteilnehmer zur Nutzung der Software und dem damit verbundenen Aufwand befragt.Ergebnisse Die Meldequote variierte zwischen den Einrichtungen sowie zwischen den Modalitäten. Aus dem Bereich der Projektionsradiografie wurden die meisten IntS-Überschreitungen gemeldet, gefolgt von der Computertomografie und der therapeutischen Intervention. IntS-Überschreitungen waren auf zahlreiche unterschiedliche Ursachen zurückzuführen, darunter auf die Einstelltechnik (19 %) sowie Bewegung oder mangelnde Kooperationsbereitschaft der Patienten (18 %). Die IntS-Überschreitungen lagen größtenteils unterhalb der gesetzlichen Meldeschwellen eines Vorkommnisses. Der Aufwand für die Erfassung wurde als angemessen bewertet.Schlussfolgerung Eine wenig aufwendige, den Anforderungen des Strahlenschutzrechts genügende und im Sinne des Risikomanagements sinnvolle Erfassung von Vorkommnissen ist möglich. Regelmäßige Schulungen zur Erkennung von Vorkommnissen und deren Abhandlung, im Umgang mit der Software und bzgl. der rechtlichen Situation aller Beteiligten, sowie ein offener Umgang mit Fehlern im Betrieb erhöhen die Anzahl an Meldungen.Kernaussagen: Zitierweise
Keywords: diagnostic radiology; QA/QC; radiation safety; CIRS; incidents; notification criteria